Synthesis and Characterization of CaO Limestone from Lintau Buo Supported by TiO2 as a Heterogeneous Catalyst in the Production of Biodiesel - Aju Deska; Syukri Syukri; Zilfa Zilfa; Novesar Jamarun; Vivi Sisca (Universitas Gadjah Mada, 2021)
Biodiesel constitutes an alternative to diesel fuel, developing a base catalyst in cost efficiency and reducing the impact on the environment due to toxic waste and excessive chemicals. This study employed a mixture of an oxide catalyst, CaO/TiO2, which was ably synthesized as a heterogeneous catalyst to convert waste frying oil (WFO) into biodiesel. Heterogeneous catalysts have been characterized by XRD, FT-IR, TEM, SEM-EDX, and BET to identify their crystal type, morphology, composition, and surface area. Catalytic activity was affected by the amount, oil/methanol ratio, reaction temperature, and duration. A 94% biodiesel yield was achieved by optimizing the following reaction parameters: 5wt.%, 6:1 methanol: oil, 65 °C, for 4 h. The addition of TiO2 to CaO improves the catalyst stability and transforms the reactants into products. The structure and characteristics of TiO2 maintained stability and supported CaO well. Its repeated biodiesel fuel production demonstrated the catalyst stability from WFO throughout the transesterification reaction.